THE INFLUENCE OF MODIFIED STRATIFICATION GROWING MEDIA AND ARBUSCULAR MYCORRHIZAL FUNGI DOSAGE ON THE ESTIMATION, YIELD, AND QUALITY OF TOMATO (LYCOPERSICUM ESCULENTUM MILL.) CROP OF SERVO F1 VARIETY - Chairunnisa, Ayundari
Tomato is a horticultural commodity that is highly demanded in Indonesia for various food and cosmetic processing purposes, with the demand for tomatoes continuously increasing each year. However, this high demand is not balanced by the quantity of tomato production. Therefore, modifications in the type of growing media and nutrient fixation formulations are needed for tomato cultivation in polybags. This research aims to analyze the influence of stratification growing media (simple huge culture) and the application of arbuscular mycorrhizal fungi dosage on the yield and fruit quality of SERVO F1 tomato variety, as well as to determine the best treatment for the yield and fruit quality of SERVO F1 tomato variety. This study employs a completely randomized factorial design with 3 factors, which are variations in the composition of the growing media (A) and the dosage of the MicroGrow endomycorrhiza (B). The results of the study show that the interaction between the stratification growing media treatment and the application of mycorrhizal fungi dosage does not significantly affect the parameters of the number of flowers in the generative phase, total harvest fruit weight, fruit diameter, and puffiness. The stratification growing media treatment has a highly significant effect on the parameter of the number of flowers (4 WAP). The application of mycorrhizal fungi dosage significantly affects the parameters of fruit diameter and puffiness (Turning-Pink). The stratification growing media treatment with a thickness of 1 cm (A3) and a mycorrhizal fungi dosage of 10 grams per plant (B1) demonstrates the best results for the estimation and yield of SERVO F1 tomatoes, while the stratification growing media treatment with a thickness of 3 cm (A2) and a mycorrhizal fungi dosage of 15 grams per plant shows the best results for the fruit quality of SERVO F1 tomato harvest.